Koherensi Hermeneutika dan Penafsiran Hukum Islam Modern - Alimuddin, Alimuddin (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2019)
This writing aimed to explain law interpretation coherence side between hermenetika pattern reasoning in western world with Islam law reasoning pattern that poured forth in system interpretation modern. In the fact, hermeneutics use model in interpretation, challenged by most Islam scholars because hermeneutics could not be used to interpret verse Al-Quran that is Islam legal source that main, differ the thing with religion law source others that berlatarbelakang essay human. To interpret al-quran and hadits, Islam has method separated that if seen by gleam view own the resemblance mode of action with hermeneutics as which have been made by Umar Ibn Khattab, even some Umar Ibn Khattab's result ijtihad if viewed cursory impressed that the decision conflict even deviate with Al-Quran. However if scanned exhaustively, Umar Ibn Khattab's decision is implication from maqasid syariyah delivery, Umar Ibn Khattab before revises a first law learn why do law levied( illat law). Can be understood that Umar's freedom ijtihad is freedom that is restricted. Pattern interpretation in Islam known with Ta'lili method reasoning namely see a implementation law based on by illat that contained in it, this pattern interpretation is identical with hermeneutics method interpretation